1992
DOI: 10.1093/jac/29.5.563
|View full text |Cite
|
Sign up to set email alerts
|

Development of resistance during ceftazidime and cefepime therapy in a murine peritonitis model

Abstract: Resistance emerging after ceftazidime or cefepime therapy was investigated in a peritonitis model. Mice were given a peritoneal challenge (10* cfu plus talcum) and treated by either antibiotic (50 mg/kg/dose, which produced similar antibiotic concentrations in peritoneal fluid in both cases). After one or three doses, resistance never developed in Serratia marcescens or Citrobacter freiouiii infections. After Enterobacter cloacae and Pseudomonas aeruginosa challenge, ceftazidime selected more resistance (21/36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…expanded-spectrum cephalosporin therapy in comparison to treatment with a ␤-lactam-␤-lactamase inhibitor combination (19,21,23,28,32). Furthermore, the resistant mutants selected during therapy comprised a heterogeneous population of not just stably derepressed mutants, as previously reported, but also mutants with resistance mechanisms other than ␤-lactamase production (4,17,34).…”
Section: Discussionmentioning
confidence: 83%
“…expanded-spectrum cephalosporin therapy in comparison to treatment with a ␤-lactam-␤-lactamase inhibitor combination (19,21,23,28,32). Furthermore, the resistant mutants selected during therapy comprised a heterogeneous population of not just stably derepressed mutants, as previously reported, but also mutants with resistance mechanisms other than ␤-lactamase production (4,17,34).…”
Section: Discussionmentioning
confidence: 83%
“…Enterobacter strains can be involved in such infections (9,31). We acknowledge that the PDI values reported here were obtained from experiments using a single E. cloacae-cephalosporin combination and that this preferential selection may not be common to all Enterobacter/Enterobacteriaceae strains (25,30). Indeed, none of the dosing regimens increased the frequency with which CZX-resistant strains of B. fragilis were isolated from the abscesses (30).…”
mentioning
confidence: 89%
“…While the ratio of the area under the concentrationtime curve (AUC) at 24 h to MIC of Ն100 (10,33,36) or a peak-to-MIC ratio of 8 to 10 (3, 8) may significantly reduce the emergence of resistant subpopulations during treatment with fluoroquinolones and aminoglycosides, it has been reported that these indices do not appear to play an important role in the suppression of resistance during ␤-lactam therapy (33). However, recent findings have indicated the importance of a high-dose, short-elimination half-life regimen to minimize the emergence of cephalosporin-resistant Escherichia coli strains (25).…”
Section: To 10mentioning
confidence: 99%
See 1 more Smart Citation
“…Often these drugs are administered in combination with aminoglycosides as a regimen for treatment of serious pseudomonal infections. Unfortunately, for each of these agents, emergence of resistance, causing treatment failure has been described during therapy (Quinn, Dudek et al 1986;Milatovic and Braveny 1987;Pechere and Vladoianu 1992;Cometta, Baumgartner et al 1994;Fink, Snydman et al 1994). Clinically significant antibiotic resistance has arisen against virtually every antibiotic developed .…”
Section: Antibiotic Resistance In Pseudomonas Aeruginosa: Strategy Tomentioning
confidence: 99%